Improving access to psychosocial interventions for common mental health problems in the United Kingdom: narrative review and development of a conceptual model for complex interventions - Gask Linda; Bower Peter; Lamb Jonathan; Burroughs Heather; Chew-Graham Carolyn; Edwards Suzanne; Hibbert Derek; Kovandžić Marija; Lovell Karina; Rogers Anne; Waheed Waquas; Dowrick Christopher; et al. (BMC, 2012)
Abstract Background In the United Kingdom and worldwide, there is significant policy interest in improving the quality of care for patients with mental health disorders and distress. Improving quality of care means addressing not only the effectiveness of interventions but also the issue of limited access to care. Research to date into improving access to mental health care has not been strongly rooted within a conceptual model, nor has it systematically identified the different elements of the patient journey from identification of illness to receipt of care. This paper set out to review core concepts underlying patient access to mental health care, synthesise these to develop a conceptual model of access, and consider the implications of the model for the development and evaluation of interventions for groups with poor access to mental health care such as older people and ethnic minorities. Methods Narrative review of the literature to identify concepts underlying patient access to mental health care, and synthesis into a conceptual model to support the delivery and evaluation of complex interventions to improve access to mental health care. Results The narrative review adopted a process model of access to care, incorporating interventions at three levels. The levels comprise (a) community engagement (b) addressing the quality of interactions in primary care and (c) the development and delivery of tailored psychosocial interventions. Conclusions The model we propose can form the basis for the development and evaluation of complex interventions in access to mental health care. We highlight the key methodological challenges in evaluating the overall impact of access interventions, and assessing the relative contribution of the different elements of the model.